1998
DOI: 10.1103/physreve.57.6761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface alignment layers on the configurational transitions in cholesteric liquid crystals

Abstract: To understand the mechanism behind the pitch change during the transient planar to the planar state transition of a cholesteric liquid crystal ͑while it is relaxing from the homeotropic state to the planar state͒, we studied a more controlled situation of pitch change in a thermochromic liquid crystal. We studied the pitch change in the liquid crystal, as a function of temperature, under various surface alignment conditions such as homogeneous and homeotropic surface alignments. In a cell with homogeneous surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…As the temperature is changed, so-called pitch jumps occur which are easily observable as changes in the selective reflection wavelength. There have been several reports of thermal hysteresis in the pitch jumps [2][3][4], as well as theoretical treatments that relate the hysteresis to parameters including surface anchoring and cell thickness [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…As the temperature is changed, so-called pitch jumps occur which are easily observable as changes in the selective reflection wavelength. There have been several reports of thermal hysteresis in the pitch jumps [2][3][4], as well as theoretical treatments that relate the hysteresis to parameters including surface anchoring and cell thickness [5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…When the temperature rises, the reflection wavelength of the cell will become shorter due to the thermodynamic vibrations effect on the original SH structure. The increased thermal vibration strength results in increased twisting power variation between the neighboring molecular structures, and the helical pitch length of the N*LC cell will be reduced [5,52]. Such a thermal vibration effect also decreases the light intensity of the Bragg reflection, which is attributed to the fact that the director of the helical axis is disturbed (i.e., it is no longer perpendicular to the substrate surface), leading to the light scattering.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the different alignment condition may result in a various response time from homeotropic state to planar state [3]. In this paper, we demonstrate the encapsulated CLC display via photo induced phase separation and investigate the influence of various UV curing conditions and cell gaps to response time of CLC display…”
Section: Introductionmentioning
confidence: 95%